MANAJEMEN PEMBIAYAAN PENDIDIKAN DI SMP - Erviana Yulianti; Aliman Aliman; Osa Juarsa (UNIVERSITAS BENGKULU, 2017)
The Objective of this study is to describe Education financial management at Junior high School 2 lubuklinggau city. The study applied the descriptive qualitative method. The subject of this study are headmaster, treasures, teacher parents and school committee, Data Collection was use through interview, Observation, and decomentation through interview, Observation and documentation technigues. The result of study showed: (1) Finacial planning education created 1 year budget. (2) Implementation of the financing done by RAPBS and reported on a quarterly basis. (3) Monitoring and evaluation of education financing is done periodically.